Water Use and Irrigation Management of Agronomic Crops: SS-AGR-155/AA131, rev. 11/2017 - Wright, D.L.; Rowland, D.; Mulvaney, M.J. (EDIS, 2017)
In order to achieve optimal yields in agronomic crops, it is imperative to maintain plants under minimal water stress. While responses to water deficits vary among different crops, the quantity of water utilized closely correlates with both vegetative growth and grain yield. Effective irrigation management aims to reduce water loss through runoff, deep percolation, and evaporation, while maximizing the portion of irrigation water allocated to crop transpiration. This document provides overarching guidelines for the efficient irrigation management of various agronomic crops in Florida.